An unusual type of polymorphism in a liquid crystal - Lin Li; Mirosław Salamończyk; Sasan Shadpour; Chenhui Zhu; Antal Jákli; Torsten Hegmann (Nature Communications, 2018)
Polymorphism is a property that allows a material to exist in two or more crystal structures. Here the authors observe thermal-induced structural polymorphism in a bent-core liquid crystal compound and show that by choosing the cooling rate, different structures with distinct structural colours are obtained.